1991
DOI: 10.1002/bjs.1800780607
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of ischaemia reperfusion injury: Central role of the neutrophil

Abstract: Ischaemia is a common clinical event leading to local and remote injury. Evidence indicates that tissue damage is largely caused by activated neutrophils which accumulate when the tissue is reperfused. If the area of ischaemic tissue is large, neutrophils also sequester in the lungs, inducing non-cardiogenic pulmonary oedema. Ischaemia reperfusion injury is initiated by production of reactive oxygen species which initially appear responsible for the generation of chemotactic activity for neutrophils. Later, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
192
1
17

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(220 citation statements)
references
References 30 publications
6
192
1
17
Order By: Relevance
“…Reperfusion after prolonged ischemia results in a metabolic insult to the affected tissue greater than the ischemic injury alone [21,58]. IRI also results in a systemic inflammatory response with the potential to affect tissues distant from the reperfused area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reperfusion after prolonged ischemia results in a metabolic insult to the affected tissue greater than the ischemic injury alone [21,58]. IRI also results in a systemic inflammatory response with the potential to affect tissues distant from the reperfused area.…”
Section: Discussionmentioning
confidence: 99%
“…effects in reperfusion injury. Neutrophil respiratory burst activity correlates to the level of neutrophil activation and ROS production [38,58]. The decrease in respiratory burst activity when animals were pretreated with NAC suggests it modulates its effects directly on the neutrophils, reducing their propensity to produce free radicals, possibly by its combined antioxidant and glutathione-replenishing activities.…”
Section: Discussionmentioning
confidence: 99%
“…The primary target of the reperfusion injury is the microcirculation where the leukocyte-endothelium interaction results in transendothelial migration and tissue injury from the release of reactive oxygen species and elastases [16,17]. Although skeletal muscle has a relatively high tolerance to ischaemia, skeletal muscle dysfunction and infarction are wellrecognised complications of the reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Endothelial dysfunction occurs as a result of tissue hypoxia and on subsequent reperfusion, cytokines and adhesion molecules are enhanced leading to chemotaxis and infiltration by neutrophils. Necrosis of damaged tissue by neutrophil myeloperoxidase (MPO) and other enzymes generates active oxygen species, which in turn can extend the ischaemic injury.…”
mentioning
confidence: 99%
“…Studies have confirmed the key role of neutrophilic infiltration in IRI. [1][2][3] Depletion of the numbers of neutrophils by haemofiltration or adhesion by immunological means can moderate IRI to a considerable extent. [5][6][7][8] Similarly, in various models of IRI, the administration of antioxidants limits the injury caused by neutrophil-derived oxygen free radicals, including systemic injury after ischaemia of the lower torso.…”
mentioning
confidence: 99%